Cinnamomum alexei Kosterm. (Lauraceae) - A new record for India - Kumar, E.S. Santhosh; Kumary, M.P. Geetha; Pandurangan, A. G. (Bangladesh Journal of Plant Taxonomy, 2011)
Keywords: Cinnamomum alexei; New record; India. DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9306 Bangladesh J. Plant Taxon. 18(2): 199-201, 2011 (December)